Kontribusi Pengrajin Jamur Tiram Putih Terhadap Pendapatan Keluarga (Studi Kasus Pada Usaha Jamur Jempol) Di Kelurahan Lancirang Kecamatan Pitu Riawa Kabupaten Sidenreng Rappang - Yusrianti Yusrianti; Nurhapsa Nurhapsa; Nurhaedah Nurhaedah (Universitas Muslim Maros, 2023)
Fungal plants in Indonesia still have the opportunity to be developed and managed properly. Oyster mushrooms in Indonesia are relatively good for cultivation, this is because the natural resources they have can be used as materials for the production of oyster mushrooms, for example sawdust as the main ingredient for making mushroom media. The purpose of this study was to determine how much the contribution of white oyster mushroom business to family income in Lancirang Village, Pitu Riawa District, Sidenreng Rappang Regency. This study uses descriptive quantitative research methods, the data used are primary data and secondary data. There are 2 samples in this study, namely workers who work in the thumb mushroom business. Then processed using contribution data analysis. From the research results obtained: that the contribution of white oyster mushroom craftsmen to family income in Lancirang Village, Pitu Riawa District, Sidenreng Rappang Regency is 35%. This shows that the contribution is classified as moderate.